Penerapan Teknologi Augmented Reality Pada Pembelajaran Sistem Saraf Bagian Otak - Muhammad Zaky Taufiq; Tommi Suryanto; Nurul Fadillah; Neny Firdyanti (Jurusan Teknik Elektro Politeknik Negeri Pontianak, 2022)
Brain is a part of the nervous system. The Nervous system has characteristics of abstract and complicated matter, because it deals with complex physical and chemical mechanisms. Therefore something is needed that can help to simplify this matter like application Augmented Reality (AR) technology. The application of AR technology to the learning of the nervous system on the brain is an android-based application that provides 3D illustrations of the brain and nerve cells so that students can see it directly and interact with the object. Method that used on development this AR application is Multimedia Development Life Cycle. Softwares that used in buildong this application are CorelDraw, Vuforia, Unity, and Visual Studio Code. The results obtained is an AR application for learning the nervous system on the brain. The tests was carried out on several students with alpha testing and beta testing methods. Based on the tests this AR application has been running well according to its function